All's fair in love and war : a novel - Heath, Virginia, 1968- (Miss Prentice's protegees, 2024)
"A new Regency romp of a series, about governess who believes in cultivating joy in her charges, clashes with the children's uncle who hired her, only to find herself falling in love. When the flighty older sister of former naval captain, Henry Kincaid, decides on a whim to accompany her explorer husband on an expedition to Egypt, he finds himself unwittingly left in the lurch with her three unruly children and her giant, mad dog. With no clue how to manage the little rascals, a busy career at the Admiralty that requires all of his attention, and no idea when his sister is coming back, Harry has to hire an emergency governess to ensure that everything in his ordered house continues to run shipshape. In desperation, he goes to Miss Prentice's School for Girls prepared to pay whatever it takes to get a governess quick sharp to bring order to the chaos. Thanks to her miserable, strict upbringing, fledgling governess Georgina Rowe does not subscribe to the ethos that children should be seen and not heard. She believes childhood should be everything that hers wasn't, filled with laughter, adventure, and discovery. Thankfully, the three Pendleton children she has been tasked with looking after are already delightfully bohemian and instantly embrace her unconventional educational ethos. Their staid, stickler-for-the-rules uncle, however, is another matter entirely. Georgina and Henry continue to butt heads over their differences, but over time it seems that in this case, their attraction is undeniable, and all is indeed fair in love and war"--